Do patients followed in anticoagulation clinics for antiphospholipid syndrome meet criteria for the disorder? - Dunn, Andrew S.; Kaboli, Peter; Halfdanarson, Thorvardur; Chan, Happy; Hubert, Rod; Rosen, Seth; White, Richard H. (Thrombosis and Haemostasis, 2005)
Although specific criteria for diagnosing the antiphospholipid syndrome (APS) exist (the Sapporo Criteria), most physicians are not aware these include repeat testing and documentation of either a lupus anticoagulant or medium to high levels of anticardiolipin antibody. Incorrect diagnosis of APS may result in unnecessary long-term anticoagulation. The purpose of this study was to determine the clinical and serological characteristics of patients being treated for APS and concordance with published criteria. This cross-sectional study identified APS patients who were being treated with warfarin at one of three universitybased anticoagulation clinics. Levels of anticardiolipin antibody were classified as low-positive if abnormal but <40 GPL/MPL units and medium/high-positive if ≥40 units. Strength of meeting Sapporo criteria was graded as definite, possible, and not meeting criteria. Of 103 cases, 97 had clinical and laboratory data available. Only 10 cases (10%, 95% Confidence Interval 5 - 19) met criteria for definite APS, 16 (16%, 10 - 26) had a possible diagnosis, and 71 (73%, 63 - 81) did not meet criteria. Of 70 cases that had abnormal anticardiolipin antibody results, only 32 (46%, 34 - 58) had medium/high-positive levels. Repeat laboratory testing was performed in only 49 cases (51%, 40 - 61). We conclude that few patients treated forAPS met Sapporo criteria. Abnormal levels of anticardiolipin antibody were frequently in the low-positive range, and repeat testing was often absent. A quality improvement program that includes review of cases referred for chronic anticoagulation care is recommended to ensure appropriate testing and treatment of patients with suspected APS.
Keywords: Antiphospholipid antibody syndrome; lupus anticoagulant; anticardiolipin antibody; anticoagulation; diagnosis